PERCEPTION OF TEACHING ETHICS IN THEPROFESSIONAL TRAINING OF PUBLIC ACCOUNTANTS, IN THE UNIVERSITIES OF HUARAZ – ANCASH, PERIOD 2024 (Lex localis - Journal of Local Self-Government, 2025)
The problem is the disagreement between the theories, ethical principles of the public accountant, and the conduct of the accounting teacher; whose objective is to interpret the perception of teaching ethics in the professional training of Public Accountants, at the universities of Huaraz – Ancash, period 2024; It was approached from the positivist paradigm with a quantitative approach; use of the quantitative method in the presentation and processing of the survey to students and for the analysis and interpretation of results;  descriptive, non-experimental and transversal research level, population of 929 students, with a probabilistic sample of 321 students; the techniques and instruments used for data collection, the survey and the questionnaire through the Likert scale; For data processing, statistical analysis – descriptive statistics and interpretation was used. The results reveal that 67% of students under study perceive that the ethics of the accounting teacher still needs to be improved in relation to ethical theories and principles. It is concluded that there is a high percentage of students who have certain reservations or feel that there is room for improvement in the ethics and conduct of the accounting teacher.